Analysis of Influence Internal Locus of Control toward Opportunity Recognition through Entrepreneurial Intention - Al Jauzi, Mohamad Refi Alamsyah; Isnawati, Isnawati; Permana, Intan; Supriyadi, Didit; Solihat, Asri (Entrepreneurship Faculty, Universitas Garut, 2024)
The concept of opportunity recognition refers to the process of identifying potential business opportunities by individuals. In recent years, the agricultural industry sector has exhibited the lowest rate of growth in comparison to other industrial sectors. The objective of this research is to enhance the capacity to analyse business opportunities with entrepreneurial intentions and self-control, with a view to developing future businesses. In this study, researchers utilised a combination of electronic mail and in-person interviews, employing a random sample of 708 individuals. The survey garnered a response rate of 84%, resulting in a total of 75 respondents who provided ratings for all items. The research instrument employed was a questionnaire comprising Likert scale statements, which were distributed through both online and direct channels, with physical questionnaires being provided to respondents. The analysis of the data was conducted using structural equation modelling (SEM). The research findings are accurate and reliable, with a significance level of 95%. The results of this study demonstrate that internal locus of control influences opportunity recognition through entrepreneurial intention. Furthermore, the results indicate that internal locus of control functions as a regulatory factor in the development of a business, entrepreneurial intention serves as a motivating factor for the establishment of a business in the future, and the ability to analyse potential business opportunities.